Expression of integrins and basement membrane components by wound keratinocytes. - Larjava, H (1993)
Extracellular matrix proteins and their cellular receptors, integrins, play a fundamental role in keratinocyte adhesion and migration. During wound healing, keratinocytes detach, migrate until the two epithelial sheets confront, and then regenerate the basement membrane. We examined the expression of different integrins and their putative ligands in keratinocytes during human mucosal wound healing. Migrating keratinocytes continuously expressed kalinin but not the other typical components of the basement membrane zone: type IV collagen, laminin, and type VII collagen. When the epithelial sheets confronted each other, these missing basement membrane components started to appear gradually through the entire wound area. The expression of integrin beta 1 subunit was increased in keratinocytes during migration. The beta 1-associated alpha 2 and alpha 3 subunits were expressed constantly by wound keratinocytes whereas the alpha 5 subunit was present only in keratinocytes during reepithelialization. Furthermore, migrating cells started to express alpha v-integrins which were not present in the nonaffected epithelium. All keratinocytes also expressed the alpha 6 beta 4 integrin during migration. In the migrating cells, the distribution of integrins was altered. In normal mucosa, beta 1-integrins were located mainly on the lateral plasma membrane and alpha 6 beta 4 at the basal surface of basal keratinocytes in the nonaffected tissue. In wounds, integrins were found in filopodia of migrating keratinocytes, and also surrounding cells in several cell layers of the migrating sheet. The results indicate that migrating keratinocytes, in deep human wounds enlarge their integrin repertoire. The changes in integrin expression take place concomitantly with changes in the basement membrane composition, suggesting a close interplay of these two groups of molecules during wound healing.